High Levels of DEAH-Box Helicases Relate to Poor Prognosis and Reduction of DHX9 Improves Radiosensitivity of Hepatocellular Carcinoma - Chen, Xi; Lin, Letao; Chen, Guanyu; Yan, Huzheng; Li, Zhenyu; Xiao, Meigui; He, Xu; Zhang, Fujun; Zhang, Yanling (Frontiers in Oncology, 2022)
Background: Liver hepatocellular carcinoma (LIHC), one of the most common primary malignancies, exhibits high levels of molecular and clinical heterogeneity. Accumulating evidence has confirmed the important roles of some RNA helicase family in tumor development, but the function of DEAH-box RNA helicase families in LIHC therapeutic strategies has not yet been clarified. Methods: The Cancer Genome Atlas (TCGA) was used to download the LIHC dataset. Consensus clustering were applied to group the patients. Least absolute shrinkage and selection operator Cox (Lasso) regression and univariate and multivariate Cox regression were used to develop and validate a prognostic risk model. Timer online databases and Tumor Immune Single Cell Hub (TISCH) were applied to explore the role of DEAH-box RNA helicases in LIHC immunotherapy. In vitro experiments were performed to explore the role of DHX9 in LIHC radiosensitivity. Results: Twelve survival-related DEAH-box RNA helicases were identified. High helicase expression levels are associated with a poor prognosis and worse clinical features. A prognostic model composed of six DEAH-box RNA helicases (DHX8, DHX9, DHX34, DHX35, DHX38, and DHX57) was constructed. It was confirmed that the risk score of this model could be an independent prognostic indicator, and that LIHC patients with different prognoses could be distinguished by the model in the training and test cohorts from TCGA. DNA repair pathways were also enriched in patients with high-risk scores. 6 DEAH-box RNA helicases from the risk model were significantly related to innate immune cells infiltration and immune inhibitors. In vitro experiments we confirmed that DHX9 knockdown improves radiosensitivity by increasing DNA damage. Conclusion: The DEAH-box RNA helicase signature can be used as a reliable biomarker for the prognosis of LIHC. In addition, DHX9 may act as trustworthy indicators and therapeutic targets in radiotherapy and immunotherapy for LIHC.